(untitled) (Research in Agriculture Livestock and Fisheries, 2017)
The present study was conducted to optimize doses of Megavit and Aquaboost on the growth performance of Thai pangas (Pangasius sutchi) in aquarium conditions. Six treatment with three replications were used (i) control; (ii) with less than recommended dose (LD) of aqua drugs (0.66 g/kg of the feed); (iii) recommended dose (RD) of aqua drugs (1 g/kg of the feed) and (iv), (v) and (vi) more than recommended doses (MRD) of aqua drugs (1.33g/ kg, 1.40 g/kg and 1.50g/kg of the feed) for 28 days in aquarium condition. In each aquarium 10 fingerlings of average initial weight 9.35 g were stocked. Feed containing either Aquaboost or Megavit, fed at 10% body weight of fish two times daily. The body weight was determined with time interval. Mortality rate also recorded. In case control feed, body weight increased slightly from initial 9.35 to 10.75g in 28 days but a positive trend in growth performance of pangas was observed after feeding different doses of aquaboost medicated diets. The highest increased body weight of 13.28±0.08g was observed in the treatment (iv) containing 1.33g/kg aquaboost in the diet of more than recommended doses where in recommended dose (iii) of 1 g/kg, the body weight of pangas increased to 11.52±0.09g. However, with the more recommended doses (MRD), (iv), (v) and (vi) in the diets, growth performance was declined. Similar results were also observed when feeding Megavit to pangas in 28 days in aquarium. Res. Agric., Livest. Fish.4(2): 117-122, August 2017